DETECT ACTIVITY OF SOME BIOLOGICAL FACTORS TO INDUCE RESISTANCE IN CANTALOUPE PLANT THROUGH PEROXIDASE ENZYME , PHENOLS AND CHLOROPHYLL CONTENTS - & et al., Hashem (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
The aim of this study was to evaluate efficiency of some biological agents to reduce charcoal rot of Cantaloupe which is caused by Macrophomina phaseolina under wooden canopy and to detect activity of inducer agents through Peroxidase enzyme, phenols and chlorophyll contents. Results obtained under Wooden canopy, treatment of combination between T.viride and B.subtilis was superior on other treatments. The disease percentage and disease severity were (0.0), (0.0)% respectively compared to control treatment (pathogen) 88.3 and 76.6% respectively. However treatment of integration between T.viride and B.subtilis was superior on other treatments in antagonism against M.phaseolina and to improve growth parameters of cantaloupe and increased wet weight and dry weight of vegetation and root to (35.0 – 4.0), (13.7 – 2.4) g/ plant respectively. Results indicated that treated plant produced phenols and peroxidase enzyme. Treatments of T.viride with B.subtilis or T.viride with A.chrococcum showed superiority in inducing peroxidase enzyme. The change in light absorbance/ min/ g .Fresh weight of cantaloupe were 81.2 and 80.6 respectively, compared to control treatment (pathogenic fungus) the activity of Peroxidase was 36.9. the same trend reflected to increase activity of phenols in treatments of T.viride with B.subtilis or T.viride with A.chrococcum reached (5.21 and 5.00) mg/g. compared with control treatment 3.6 mg/g. The result, also showed that all treatments increased chlorophyll content. Integration between T.viride and B.subtilis achieved highest chlorophyll content (56.3) Spad.